Lymphatic treatments after orthopedic surgery or injury: A systematic review. Issue 4 (October 2020) - Klein, Ifat; Tidhar, Dorit; Kalichman, Leonid
Abstract: Background: Orthopedic injuries in conjunction with extensive damage to tissues, bones and blood vessels, usually require a long recovery. Associated consequences are pain, movement limitations, decreased function and occasionally, prolonged edema, which can delay or interfere with the healing process. Lymphatic and compression therapy have become increasingly common, intending to reduce edema and pain, thus, promoting the recovery process. Aims: To examine the efficacy of methods commonly used to reduce edema after orthopedic injury or surgery, i.e. decongestive therapy, manual lymphatic drainage, and compression bandaging. Methods: English literature search was undertaken in January 2019, in the following databases: Cochrane Library, MEDLINE, PEDro. Inclusion criteria: randomized controlled or quasi-controlled trials in adults who have edema or pain after recent limb trauma or surgery. Two independent assessors rated study quality and risk of bias using the PRISMA recommendations and PEDro score. Results: We evaluated 71 papers. After excluding duplicated and irrelevant papers, 15 met the eligibility criteria (6 on lymphatic treatment and 9 on compression). Quality of papers ranged from 3 to 7 on PEDro score; of them, 13 were 1b Level of Evidence and two were 1c. Conclusion: After elective surgeries, when the significant edema appears or persists beyond recovery time, complex decongestive therapy and manual edema mobilization should be recommended in addition to conventional physical therapy. In acute injuries such as ankle or distal radius fractures, lymphatic treatments and compression bandaging should be considered as part of the therapeutic protocol. Nine studies evaluated different compression modalities found that only multilayer and long stretch compression significantly reduce edema.